Plastic additive bisphenol S induces depression by promoting AZU1/CTSD proteins to mediate plasma-related proteins and metabolites: A comprehensive multi-omics analysis - Ni-ren Li; Pai Xie; Yi-xuan Zeng; Bing-ying Deng; Si-fan Lu; Yu-feng Gu; Yanhong Ma; Chao-hua Luo; Yi Liu (Ecotoxicology and Environmental Safety, 2025)
Background: The role of bisphenol S (BPS) in the pathogenesis of depression still unclear, particularly regarding its underlying mechanisms and causality. Methods: In this study, network toxicology approaches were employed to explore the mechanisms underlying BPS-induced depression, and Mendelian randomization (MR) was utilized to validate the causal relationship between BPS-targeted proteins and depression. Clinical datasets were further analyzed to corroborate the identified proteins. Molecular docking and molecular dynamics (MD) simulations were conducted to assess the binding stability between BPS and its target proteins. To investigate potential mediating pathways through which BPS-targeted proteins might contribute to depression, multi-omics data were integrated, including proteome-wide association study datasets from the FINNGEN biobank, the UK Biobank Pharma Proteomics Project, and the Icelandic deCODE consortium, as well as human plasma metabolomic datasets. This enabled a systematic exploration of the mediating roles of plasma proteins and metabolites in the association between BPS-targeted proteins and depression. Finally, protein-protein docking simulations were performed to validate interactions among key proteins. All analyses adhered to rigorous scientific standards for reproducibility and validity. Results: BPS impaired the blood-brain barrier and exerted adverse effects on the brain. Network toxicology analysis revealed that BPS promotes the onset of depression by modulating pathways including neuroactive ligand-receptor interaction, calcium signaling pathway, cAMP signaling pathway, PI3K-Akt signaling pathway, and apoptosis. Using MR, molecular docking, MD simulations, and clinical data validation, we demonstrated that BPS stably binds to its target proteins, AZU1 and CTSD, and exhibits a significant causal relationship with depressive symptoms. Mediation MR analysis further revealed that AZU1 promotes depression by mediating the expression of plasma proteins CD302 and FGF19, as well as the production of the plasma metabolite phosphate to urate ratio. Similarly, CTSD mediates the depressive effects by regulating plasma metabolite levels, including cysteinylglycine disulfide, oxidized Cys-gly, X-11470, cysteinylglycine to taurine ratio, and aspartate to mannose ratio. Conclusions: This study elucidates the mechanistic pathways through which the plastic additive BPS induces depression, providing critical insights into its adverse effects on the brain. These findings hold significant implications for public health safety and offer a comprehensive research framework and novel perspectives for evaluating the safety of plastic additives.